Autistic phenomenology: past, present, and potential future - Green, Jonathan; Shaughnessy, Nicola (Frontiers in Psychology, 2023)
This paper takes a broad view of the history of phenomenological perspectives on the autism concept, and how this has evolved over time, including contemporaneous theory and methods. Early inquiry from a clinical perspective within the tradition of classical continental phenomenology, linked closely to consideration of schizophrenia, is contrasted with emerging observations of child development, and a period in the second half of the 20 th century of scientific inquiry into a behavioural autistic phenotype in which there was little or no phenomenological aspect; a phenotype that has determined the recent scientific and clinical conceptualisation of autism within current nosology. This paper marks then a more recent reawakening of interdisciplinary interest in subjective experience and phenomenological inquiry, which itself coincides with the increasing prominence and salience of the neurodiversity movement, autistic advocacy, and critical autism studies. We review this emerging phenomenological study, alongside a contemporaneous clinical phenomenology perspective and representations of autistic experience from within the extensive literature (including life writing) from autistic people themselves; all perspectives that we argue need now bringing into juxtaposition and dialogue as the field moves forward. We argue from this for a future which could build on such accounts at greater scale, working towards a more co-constructed, systematic, representative, and empirical autistic phenomenology, which would include citizen science and participatory science approaches. Success in this would not only mean that autistic experience and subjectivity were re-integrated back into a shared understanding of the autism concept, but we also argue that there could be the eventual goal of an enhanced descriptive nosology, in which key subjective and phenomenological experiences, discriminating for autism, were identified alongside current behavioural and developmental descriptors. Such progress could have major benefits, including increased mutual empathy and common language between professionals and the autistic community, the provision of crucial new foci for research through aspects of autistic experience previously neglected, and potential new supportive innovations for healthcare and education. We outline a potential programme and methodological considerations to this end.